Effect of the TiC content on microstructure and thermal properties of Cu-TiC composites prepared by powder metallurgy - Buytoz, Soner; Dagdelen, Fethi; Islak, Serkan; Kok, Mediha; Kir, Durmus; Ercan, Ercan (Springer, 2014)
Copper matrix with an individual addition of TiC particles was prepared by means of powder metallurgy and hot pressing process, and the effect of TiC addition on microstructure, thermal properties, and electrical conductivity of Cu-TiC composites was investigated. The TiC quantity was changed as 1, 3, 5, 10, and 15 Cu (in mass%), and Cu-TiC powder mixtures were hot-pressed for 4 min at 700 A degrees C under an applied pressure of 50 MPa. Microstructure studies revealed that TiC particles were distributed uniformly in the Cu matrix. Thermal Analysis result showed that there were two exothermic peaks and with rising TiC rate, oxidation amount of Cu composite decreased. With the increasing addition of TiC, hardness of composites changed between 58.6 HV0.1 and 87.8 HV0.1. The highest electrical conductivity for Cu-TiC composites was obtained in the Cu-1 mass% TiC composite, with approximately 81.2 % IACS.
Keywords: Hot pressing; Cu-TiC; Microstructure; Thermal properties; Electrical conductivity